Analysis of Misbehaviors and Satisfaction With School in Secondary Education According to Student Gender and Teaching Competence - Granero-Gallegos, Antonio; Baños, Raúl; Baena-Extremera, Antonio; Martínez-Molina, Marina (Frontiers in Psychology, 2020)
Effective classroom management is a critical teaching skill and a key concern for educators. Disruptive behaviors disturb effective classroom management and can influence school satisfaction if the teacher does not have the competencies to control them. Two objectives were set in this work: to understand the differences that exist in school satisfaction, disruptive behaviors, and teaching competencies according to the gender of the students; and to analyze school satisfaction and disruptive student behaviors based on perceived teaching competence. A non-probabilistic and convenience sample selection process was employed, based on the subjects that we were able to access. 758 students participated (male = 45.8%) from seven public secondary schools in the Murcia Region (Spain). The age range was between 13 and 18 years (M = 15.22; DT = 1.27). A questionnaire composed of the following scales was used: Competencies Evaluation Scale for Teachers in Physical Education, School Satisfaction and Disruptive Behaviors in Physical Education. Mixed Linear Models performed with the SPSS v.23 was used for statistical analyses. The results revealed statistically significant differences based on gender and physical education teaching competencies. In conclusion, the study highlights that physical education teacher skills influence disruptive behaviors in the classroom, and that this is also related to school satisfaction. Furthermore, it highlights that boys showed higher levels of negative behaviors than girls.